Exploring the effect of soybean fermentation broth (S-FB) on gut microbes of lipopolysaccharide (LPS)-infected loach (Misgurnus anguillicaudatus) using 16S rRNA sequencing - Chu, Shenghui; Fan, Ruike; Dai, Lishang; Liu, Min (Frontiers in Microbiology, 2025)
The fermentation products of soybean are rich in beneficial bacteria, which play Shenghui Chu a significant role in maintaining the balance of intestinal microbiota and improving intestinal health. To investigate the immunomodulatory effects of soybean fermentation broth (S-FB) on loach (Misgurnus anguillicaudatus) with lipopolysaccharide (LPS)-induced enteritis, 16S rDNA high-throughput sequencing technology was employed to analyze the composition and structure of intestinal microbiota in two groups: the LPS-treated group (fed with soybean broth) and the control group (normal feeding conditions). The results revealed that the relative abundance of beneficial bacteria, such as Lactobacillus and Muribaculaceae, significantly increased in the treatment group, while the relative abundance of harmful bacteria, including Aeromonas and Shewanella, decreased. These findings suggest that soybean fermentation broth can repair intestinal damage and maintain intestinal health by enhancing the abundance of beneficial bacteria and reducing the pathogenic effects of harmful bacteria on the host. Functional prediction studies of microbial communities also showed that treatment groups primarily affected metabolic and genetic information processing. The research results analyzed the changes in the structure and distribution of intestinal microflora in different groups of loach, providing new insights into the possible role of soybean fermentation liquid in intestinal inflammation.